Flags of our fathers [videorecording (Blu-Ray)] - Eastwood, Clint, 1930-; Broyles, William, Jr., 1944-; Haggis, Paul; Phillippe, Ryan, 1974-; Bradford, Jesse; Beach, Adam, 1972-; Hickey, John Benjamin; Pepper, Barry, 1970-; Bell, Jamie, 1986-; Walker, Paul, 1973-2013; Cross, Joseph, 1986-; Walker, Benjamin, 1982-; et al. (Warner Bros. Pictures, 2007)
The story of the five Marines and one Navy corpsman that were forever immortalized as a symbol of WWII by raising the American flag at the battle of Iwo Jima. When Joe Rosenthal's photograph of the event becomes a symbol of hope for the families at home, the three surviving men are pulled from combat and sent on a tour across America to raise desperately-needed bond money. It is a trip that brings out the truths of both that symbolic act, and of their lives during war.